Functional outcome and complications following surgery for Dupuytren's disease: a multi-centre cross-sectional study. (January 2017) - Rodrigues, J. N.; Zhang, W.; Scammell, B. E.; Chakrabarti, I.; Russell, P. G.; Fullilove, S.; Davidson, D.; Davis, T. R. C.
Variables associated with recurrent Dupuytren's disease, or a 'diathesis', have been investigated, but those associated with functional outcome and complications are less well studied. Outcomes 1 or 5 years after an aponeurotomy, fasciectomy or dermofasciectomy were assessed by patient interview and examination at five UK centres. A total of 432 procedures were studied. The reoperation rate did not differ at 1 year ( p = 0.396, Chi-square test with Monte Carlo simulation), but was higher after aponeurotomy in the 5-year group (30%, versus 6% after fasciectomy and 0% after dermofasciectomy, p = 0.003, Chi square test with Monte Carlo simulation). Loss of function (DASH>15) did not differ between procedures at 5 years, even when reoperation and other variables were controlled. Diabetes, female gender and previous ipsilateral surgery were associated with poorer function in logistic regression analysis. The variables associated with poor function after treatments differ from diathesis variables. Aponeurotomy had lower complication rates than fasciectomy and dermofasciectomy. This may counterbalance the former's higher recurrence rate and explain why aponeurotomy demonstrated similar long-term functional outcome compared with excisional surgery in this study. Level of evidence: III